EKSTRAKSI MINYAK ATSIRI BUNGA MELATI DENGAN MENGGUNAKAN PELARUT ISOPROPIL ETER : PENGARUH WAKTU, TEMPERATUR, DAN RASIO MASSA BUNGA MELATI DENGAN VOLUME PELARUT - Febrina Iskandar, Michael Dillo Rizki Ginting, Iriany, Okta Bani (Jurnal Teknik Kimia USU, 2019)
Jasmine flower is one of the high value commodities. One of the applications of  jasmine flower  is jasmine essential oil. Jasmine essential oil is often used to produce high quality parfume. Extraction is one of the methods for extracting jasmine essential oil, usually by the help of solvent. In this study, the effect of extraction time, extraction temperature, and solvent to jasmine flower ratio on jasmine oil extraction was studied. The extraction was carried out at 30oC, 35oC, and 40oC for 2 hours, 3 hours, 4 hours, and 5 hours by using isopropyl ether. The ratio of jasmine flower to isopropyl ether were 1:3; 1:4; and 1:5 (m/v). The resulting jasmine oil was analyzed by GC-MS and its quality was assessed according to SNI 06-2385-2006 which include colour test, refractive index analysis, acid number analysis, and ester number analysis. This experiment showed that increasing of extraction time, extraction temperature, and volume of solvent lead to increase of absolute yield of jasmine essential oil. The highest jasmine oil yield was obtained at 10.63 %. The jasmine oil contained 45.34% benzyl acetate and had yellow color. Its refractive index, acid number, and ester number were 1.485, 26.228 mg KOH/gram jasmine essential oil, and 159.885 mg KOH/gram jasmine essential oil.